2008
DOI: 10.1097/jsm.0b013e31816d78c1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Neoprene Knee Sleeve on Subjects With a Poor Versus Good Joint Position Sense Subjected to an Isokinetic Fatigue Protocol

Abstract: Bracing is helpful in individuals with a poor baseline proprioceptive acuity in both fatigued and nonfatigued states. Subjects with a good joint position sense benefit from bracing only when in a fatigued state. The present findings suggest a rationale for using neoprene knee sleeves as a preventative measure or treatment in subjects and patients to enhance proprioceptive acuity in a fatigued state. Classification into "poor" and "good" proprioceptive acuity is only relevant in the nonfatigued condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
3
20
0
2
Order By: Relevance
“…Separating the subjects with poor joint position sense without knee support the improvement in proprioception wearing the brace and the sleeve was significant after uphill as well as after downhill walking. These results are consistent with the studies of Van Tiggelen et al [16,17]. Subjects with a good proprioceptive acuity do not benefit from the use of knee supports.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Separating the subjects with poor joint position sense without knee support the improvement in proprioception wearing the brace and the sleeve was significant after uphill as well as after downhill walking. These results are consistent with the studies of Van Tiggelen et al [16,17]. Subjects with a good proprioceptive acuity do not benefit from the use of knee supports.…”
Section: Discussionsupporting
confidence: 92%
“…The present study concerns trained young people who are supposed to have a good proprioceptive acuity. The effect of the knee supports might be even stronger for untrained, injured or aged people with lower proprioceptive acuity [14,16,17]. Moreover, the subjects walked on a treadmill with a constant inclination and an even ground and it should be accounted as a limitation when relating the results with a real hiking situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuromuscular fatigue during sustained static or dynamic contractions is an important limiting factor in the development of performance in many occupations including sports 6,7 . There are different protocols able to promote muscular fatigue, however, Isokinetic fatigue protocols are 8-10 currently considered as a gold standard in clinical and sports approaches [11][12][13] .…”
Section: Original Article Artigo Original Artículo Originalmentioning
confidence: 99%
“…Schwendner et al 14 reported that no fallers have greater muscle endurance (maximal knee extensions until force output, 50% of maximal voluntary contraction for two consecutive repetitions) than fallers (95 vs. 81 sec). Thus, muscle fatigability may be an important determinant of physical function, although few studies 11,13 the rate-limiting precursor of carnosine, has been shown to elevate the muscle carnosine content. We aimed to investigate, using proton magnetic resonance spectroscopy (proton MRS were found that evaluated the fatigability on active and inactive subjects.…”
Section: Original Article Artigo Original Artículo Originalmentioning
confidence: 99%